Comparison of Quality of Life and Sexual Function between Pelvic Organ Prolapse Patients Using Pessary and Surgical Intervention - Setyawan Nurtanio; RM Sonny Sasotya; M. Rizkar Aref Sukarsa; Eppy Darmadi Achmad; Andi Rinaldi; Aria Prasetya Ma'soem; Kania Praharsini (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objective: This study aims to compare the improvement in QoL (measured by PFDI-20) and sexual function (measured by FSFI) in POP patients (stage II-IV) treated with either surgical intervention or pessary insertion.Methods: The study employed a quasi-experimental pre–posttest design involving 60 patients with stage II–IV pelvic organ prolapse (POP), consisting of 30 patients in the surgical group and 30 patients in the pessary group, conducted at two tertiary referral hospitals in Bandung. Quality of life and sexual function were assessed using the Pelvic Floor Distress Inventory-20 (PFDI-20) and the Female Sexual Function Index (FSFI) before and three months after the intervention. Statistical analyses included paired t-tests to evaluate within-group changes before and after the intervention and independent t-tests to compare post-intervention outcomes between the two groups.Results: The results demonstrated that both the surgical group and the pessary group showed significant improvements in quality of life and sexual function (p<0.001). In the surgical group, the FSFI score increased from 16.46 ± 6.88 to 27.68 ± 3.17, surpassing the threshold for normal sexual function, while the PFDI-20 score decreased from 114.34 ± 57.44 to 14.93 ± 7.37. The pessary group also showed significant improvement, with the FSFI score increasing from 18.69 ± 4.76 to 24.80 ± 3.83 and the PFDI-20 score decreasing from 130.24 ± 48.80 to 36.98 ± 21.37. Post-intervention comparative analysis showed statistically better outcomes in the surgical group for both the FSFI score (p=0.002) and the PFDI-20 score (p<0.001).Conclusion: Both surgical and pessary interventions are effective in improving the quality of life and sexual function in women with pelvic organ prolapse. Surgical intervention, however, offers superior and lasting outcomes. Pessary usage remains an important non-surgical option for patients seeking conservative management. AbstrakTujuan: Penelitian ini bertujuan membandingkan perubahan kualitas hidup dan fungsi seksual pada pasien POP stadium II–IV yang menjalani terapi bedah dan penggunaan pessarium.Metode: Metode penelitian yang digunakan yaitu kuasi-eksperimental dengan desain pre–posttest yang dilakukan pada 60 pasien POP stadium II–IV, terdiri atas 30 pasien kelompok bedah dan 30 pasien kelompok pessarium, di dua rumah sakit rujukan tersier di Bandung. Penilaian kualitas hidup dan fungsi seksual dilakukan menggunakan kuesioner Pelvic Floor Distress Inventory-20 (PFDI-20) dan Female Sexual Function Index (FSFI) sebelum dan tiga bulan setelah intervensi. Analisis statistik menggunakan uji t berpasangan untuk menilai perubahan sebelum dan sesudah intervensi pada tiap-tiap kelompok serta uji t tidak berpasangan untuk membandingkan luaran pascaintervensi antar kelompok.Hasil: Hasil penelitian menunjukkan bahwa kelompok dengan terapi bedah dan kelompok dengan pessarium menunjukkan peningkatan bermakna pada kualitas hidup dan fungsi seksual (p<0,001). Pada kelompok bedah, skor FSFI meningkat dari 16,46 ± 6,88 menjadi 27,68 ± 3,17, melewati ambang fungsi seksual normal, sedangkan skor PFDI-20 menurun dari 114,34 ± 57,44 menjadi 14,93 ± 7,37. Kelompok pessarium juga menunjukkan perbaikan yang bermakna, dengan peningkatan skor FSFI dari 18,69 ± 4,76 menjadi 24,80 ± 3,83 dan penurunan skor PFDI-20 dari 130,24 ± 48,80 menjadi 36,98 ± 21,37. Analisis perbandingan pascaintervensi menunjukkan hasil yang secara statistik lebih baik pada kelompok bedah baik untuk skor FSFI (p=0,002) maupun PFDI-20 (p<0,001).Kesimpulan:Terapi bedah dan penggunaan pessarium secara bermakna meningkatkan kualitas hidup dan fungsi seksual pada pasien prolaps organ panggul. Terapi bedah memberikan perbaikan yang lebih besar dan lebih menyeluruh, sedangkan penggunaan pessarium tetap merupakan pilihan nonbedah yang efektif dan aman pada pasien terpilih.